META-ANALYSIS: THE EFFECT OF TECHNOLOGY ACCEPTANCE MODEL ON GENERATION Z'S ONLINE SHOPPING INTENTION - Yolanda Veybitha; Yusro Hakimah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Generation Z dominates online purchases, this is because their daily lives are inseparable from gadgets. Mastery of technology is needed in order to be able to make online purchases. The purpose of this review is to draw conclusions about the online purchase intention behavior of Generation Z which is influenced by the Technology Acceptance Model (TAM). Generation Z is closely related to the digital world because they were born and grew up in the digital era. TAM has a role in the formation of online generation purchase intention behavior, therefore the author tries to review several studies both at home and abroad to draw generalizations about the online purchase intention behavior of generation Z. The method used in this review is a meta-analysis that summarizes There have been several studies over the last 15 years regarding the effect of TAM on Generation Z's online purchase intention. The review results show that the Technology Acceptance Model (TAM) has a significant effect on Generation Z's online purchase intention, although there are several studies showing insignificant results. This is because there are other factors that influence such as trust or comfort.